Riding the tiger : Ramiro de Leon Carpio's battle for human rights in Guatemala - Llosa, Alvaro Vargas; Aroca, Santiago; Vargas Llosa, Alvaro (Miami, Fla. : Brickell Communications, 1995)
"Highly favorable (self-)portrait of human rights activist who became president of Guatemala following legislative coup against predecessor Jorge Serrano Elias (1991-93). Based on interviews with Vargas Llosa and Aroca, includes flattering prologue and epilogue and reprinted dispatches from Guatemala"--Handbook of Latin American Studies, v. 58.
"Translated from an unpublished transcript by Carlos Verdecia"--T.p. verso.
Includes index.
Interview with the President of Guatemala.
Keywords: Leon Carpio, Ramiro de -- Interviews; Leon Carpio, Ramiro de; Human rights -- Guatemala -- History; Presidents -- Guatemala -- Interviews; Guatemala -- Politics and government -- 1985-